John Lennon - White, Michael, 1959- (San Diego : Blackbirch Press, 2004)
Reviews the life and work of legendary rock musician John Lennon, from his childhood in Liverpool to superstardom as a member of the Beatles and as a solo artist, as well as his promotion of world peace.
Includes discography (p. 62) and index.
Keywords: Lennon, John, -- 1940-1980 -- Juvenile literature; Rock musicians -- England -- Biography -- Juvenile literature; Musicians -- Juvenile literature; Rock music -- Juvenile literature